2009
DOI: 10.2217/fnl.09.32
|View full text |Cite
|
Sign up to set email alerts
|

Association of Epilepsy and Comorbid Conditions

Abstract: Comorbid health conditions are common among people with epilepsy. Proposed explanations for this association include the possibility that first, epilepsy (including its treatment) causes the comorbid condition; second, the comorbid condition (including its treatment) causes epilepsy; or third, a common pathogenic mechanism mediates the co-occurrence of epilepsy and the comorbid condition. It is unlikely that a single explanation will suffice for all of the epilepsy comorbid conditions. Determining the basis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0
9

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(75 citation statements)
references
References 53 publications
(52 reference statements)
2
64
0
9
Order By: Relevance
“…Epilepsy-related health-care costs in our study accounted for b 40% of total observed health-care costs, which suggests that comorbid conditions may be costly and/or that epilepsy-related health-care utilization was underidentified. Timely surveillance and treatment of comorbid conditions in adults with epilepsy are important because co-occurring conditions can be the cause of seizures (e.g., cerebrovascular disease) or can be exacerbated by epilepsy (e.g., neurodegenerative diseases), and poor control of comorbidities may further complicate the overall management of the disease, leading to an increased economic burden [1,[17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Epilepsy-related health-care costs in our study accounted for b 40% of total observed health-care costs, which suggests that comorbid conditions may be costly and/or that epilepsy-related health-care utilization was underidentified. Timely surveillance and treatment of comorbid conditions in adults with epilepsy are important because co-occurring conditions can be the cause of seizures (e.g., cerebrovascular disease) or can be exacerbated by epilepsy (e.g., neurodegenerative diseases), and poor control of comorbidities may further complicate the overall management of the disease, leading to an increased economic burden [1,[17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…В целом у детей с эпилепсией распространенность сопутствующих заболеваний, в том числе различных нейропсихиатрических нарушений, значительно вы-ше, чем у здоровых детей [32,33,57,61,64]. По мне-нию авторов, СДВГ и другие психиатрические рас-стройства, такие как расстройства настроения, тревожные расстройства и психотические заболева-ния, -наиболее распространенные сопутствующие заболевания у пациентов с эпилепсией.…”
Section: историческая справкаunclassified
“…По мнению М. Seidenberg et al (2009), связь между эпилепсией и сопутствующим заболеванием можно рассматривать в трех плоскостях [64]. Эпилепсия (или ее лечение) может стать причиной сопутствую-щего заболевания, а сопутствующее заболевание (или его лечение) может стать причиной эпилепсии.…”
Section: историческая справкаunclassified
“…Because it can be dif fi cult for physicians to differentiate seizures from various other conditions, neuropsychologists are likely to evaluate patients who have not yet received a de fi nitive diagnosis. It also is important to keep in mind that two different disorders may coexist in the same patient [ 65 ] .…”
Section: Diagnostic Challengesmentioning
confidence: 99%